El Judgment of admissibility in Brazil’s federal disciplinary administrative process: Analysis on crimes of abuse of authority (Legal journal - Research in Legal and Social Sciences, 2021)
It can be said that the purpose of a summary administrative investigation is to enable the robust design of the judgment of admissibility, and to avoid reckless and confusing disciplinary procedures that turn everlasting in violation of individual rights and guarantees. Thus, it is no longer about an accusatory correctional lawsuit, but about the prior summary investigation, which represents a guarantee to public servants to prevent precipitated accusatory proceedings or summary administrative investigations that have a different outcome ultimately. To this end, this paper applies a methodology of qualitative approach, descriptive and non-experimental; the data collecting technique is the documentary observation and bibliographic review of current legislation, case law and doctrine, since the objective set out in this paper is the analysis of the federal disciplinary administrative process in the face of Act number 13.869/19. The mentioned Act covers the subject of abuse of authority, which requires the attention of Public Administration regarding the preconditions for a punitive process and its duration, what makes indispensable the ensemble of administrative actions to make an exemplary judgment of admissibility. This article represents a contribution in the field of comparative law for the application of norms in this category.
Keywords: administrative process; judgment of admissibility; crime; abuse of authority